The Crisis of Culture: Recovering Shared Meaning - Imogen Sinclair (Religions)
French political scientist Olivier Roy maintains that the West is undergoing a ‘crisis of culture’. The crisis derives from a process of ‘deculturation’ where superficial, deterritorial subcultures become the basis for shared understanding, rather than values. Roy maintains that this is a ‘dehumanising’ process. This paper seeks to understand by what means the West might recover a culture. This question demands understanding the concept itself, including its relationship to things material and transcendent. Drawing on the work of the 20th century Jesuit priest and theologian Henri de Lubac, as well as contemporary theologians like John Milbank and Carmody Grey, the paper will base its conclusions on the idea that nature and grace are correlative terms, and culture is not opposed to either. Such a conclusion, however, requires a certain religious logic that is rare in current philosophical discourse. A catholic understanding of the human can help to weave back nature, grace and culture into a proper relationship which does not isolate the natural from the supernatural, and informs the remaking of a culture shaped by Christian humanism.